2008
DOI: 10.1007/s00122-008-0879-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AT-rich microsatellites in common bean (Phaseolus vulgaris L.)

Abstract: Polymorphism of microsatellite markers is often associated with the simple sequence repeat motif targeted. AT-rich microsatellites tend to be highly variable and this appears to be notable, especially in legume genomes. To analyze the value of AT-rich microsatellites for common bean (Phaseolus vulgaris L.), we developed a total of 85 new microsatellite markers, 74 of which targeted ATA or other AT-rich motif loci and 11 of which were made for GA, CA or CAC motif loci. We evaluated the loci for the level of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
80
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(94 citation statements)
references
References 49 publications
9
80
1
4
Order By: Relevance
“…The ME1 marker was initially marked in LG 1 by Blair et al (2008) and then reported in LG 9, and is present in the linkage map published by Galeano et al (2009) and Blair et al (2010). In this study, ME1 was found near a QTL (2.29 cM) and showed an effect of increasing resistance to white mold, but with low heritability (0.55%).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The ME1 marker was initially marked in LG 1 by Blair et al (2008) and then reported in LG 9, and is present in the linkage map published by Galeano et al (2009) and Blair et al (2010). In this study, ME1 was found near a QTL (2.29 cM) and showed an effect of increasing resistance to white mold, but with low heritability (0.55%).…”
Section: Discussionmentioning
confidence: 50%
“…The BM184 marker was initially mapped in LG 11 (Blair et al, 2003(Blair et al, , 2008. However, Maxwell et al (2007) identified this marker in LG 9, evaluating the RIL G122/CO72548 population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent were AG, GAA, CAT, TGG motifs. Blair et al (2008) developed 85 new SSRs, 71 were developed from an ATA-enriched library, 3 AT-rich SSRs from gene-based sequences and 11 were based on non-AT-rich sequences and were made for GA, CA or CAC motif loci. A total of 45 new loci could be mapped on the DG integrated map and this brings to over 160 mapped loci for common bean with the previous genetic mapping of SSRs conducted by Yu et al (2000), Blair et al (2003) and Grisi et al (2007).…”
mentioning
confidence: 99%
“…They integrated 99 new BMb markers into the genetic map with a high LOD score with the most common motifs AT/TA and ATA/TAT. The new genetic map had a total of 215 SSRs and included 116 previously mapped SSR loci from Blair et al (2003Blair et al ( , 2008. Hanai et al (2010) developed a set of new 282 markers (50 EST-SSR, 32 RGA (resistance gene analogs), and 200 AFLP) and a new, expanded version of the core linkage map, using the BJ population.…”
mentioning
confidence: 99%